Diagnostic Role of Lymphnode Imprint: A Cyto-histopathological Correlation - Choudhary, Prabesh Kumar; Nepal, Niraj; Mainali, Nirajan; Chhetri, Gaurav (Nepalese Medical Journal, 2019)
Introduction: Lymphadenopathy is a very common condition for which excision biopsy is often recommended when fine needle aspiration cytology is not conclusive. Lymph node imprint cytology is a useful and rapid alternative diagnostic tool. This study was conducted to assess the accuracy of lymph node imprint cytology as compared to the histopathology. Materials and Methods: Imprint smears were made from all cases of lymphadenopathy. The smears were evaluated by three pathologists and categorized into, inflammatory lesions and primary and metastatic tumors. Imprint smears were made from lymph node excision specimens and were stained with PAP and MGG stains. The diagnosis in imprints was compared with those given by histopathology. With the help of sensitivity, specificity & accuracy, the agreement between the imprint smear and histopathology was determined. Results: Among the total 92 cases, 40 (43.4%) cases were chronic non-specific lymphadenitis, 22 (23.9%) were tuberculosis and metastatic lesions each. The overall accuracy of lymph node imprint cytology was 96.73%, 96.74%, 96.74% and 100% for tuberculosis, chronic non-specific lymphadenitis, lymphoma, and metastatic lesions respectively. Conclusions: Lymph node imprint smears is a rapid diagnostic tool and can be used routinely as an adjunct to histopathology in the diagnosis of various lymph node disorders.